(untitled) (Journal of Pakistan Orthopaedic Association, 2015)
Objective: To determine the association of clubfoot with consanguinity, ethnicity, lunar eclipse and addictions. Methods: This observational descriptive case series study was conducted from July 2013 to December 2013. All 200 idiopathic clubfoot patients, who reported at Clubfoot Clinic (CFC) were included in the study. A designed questionnaire was used for asking questions from parents on telephone and during their visit to CFC Results: Eighty-five (42.5%) patients were born from consanguineous marriage and 115 (57.5%) from non- consanguineous marriage. (p<0.001) 10 out of 115 consanguineous marriage were non- Muslim, who do not marry cousins (p<0.001) Two mothers had a history of smoking during pregnancy, 16 had a habit of chewing Paan (beetle nut & tobacco). None of the mothers had exposure to lunar /solar eclipse. Conclusion: The Club Foot has a strong association with consanguine marriages, with heterogenic geographical distribution and family history and no association to exposure with lunar eclipse. Association with addiction (cigarette smoking tobacco chewing & paan), could not be identified due to insufficient data. Key Words: Clubfoot, Consanguinity, Ethincity, and Addiction